Management Accounting 1980: Proceedings of the University of Illinois Management Accounting Symposium (Book). - Burns, Thomas J.; Hilton, Ronald W. (The Accounting Review, 1981)
Reviews the book "Management Accounting 1980: Proceedings of the University of Illinois Management Accounting Symposium," by H. Peter Holzer.